The Decline of Islamic Libraries in the Middle Eastern Civilization During the Crusades - Edgar Restu, Reza Nawafella Alya Parangu, (UIN Raden Intan Lampung, 2024)
The Crusades that took place between the 11th and 13th centuries had a huge impact not only on politics and the military, but also resulted in serious damage to Islamic libraries in the Middle East. Attacks on major cities such as Jerusalem, Cairo, and Baghdad caused many libraries to be destroyed, with many manuscripts and scholarly works lost to looting and fire. In addition, many scientists and scholars fled, which reduced the interaction and exchange of knowledge that had previously existed. This collapse had long-term effects, seen in the decline of scientific production and the change in focus of scientists to more practical fields, such as medicine and engineering, rather than pure science. While some Muslim scientists began to collaborate with European scientists, many discoveries and innovations from the Islamic scientific tradition could not continue, creating a gap in the development of science. This study uses literature analysis to understand the impact of the Crusades on Islamic libraries and intellectual traditions. The results show that the destruction of Islamic libraries not only caused a great loss of knowledge, but also affected the development of future thought and science. Understanding this history is important to preserve and protect cultural heritage and knowledge so that similar tragedies are not repeated, and to ensure that valuable knowledge remains accessible and is passed on to future generations.Keywords: Keywords consist of three to five relevant words/phrases separated by semicolon